Intangible Cultural Heritage of Manabí (Ecuador): Vulnerability and Actions for Safeguarding - Mendoza Mendoza, Blanca Enith (2025)
Introduction: The research focuses on the preparation of an inventory of the Intangible Cultural Heritage (ICH) of Manabí, with the objective of documenting and preserving its tangible and intangible heritage. Main objective: Promote the development of authentic and sustainable tourist experiences through the preservation and documentation of the ICH of Manabí. Method and technique: Two main tools were used: first, the National Institute of Cultural Heritage (INPC) instructions for registration and inventory forms, and second, Georeferencing Systems (GIS) along with the SURVEY 123 application, which facilitated data collection using smart digital forms. Results: A database of ICH georeferencing and a proposal for actions for its safeguarding and sustainable tourism development, aligned with the Sustainable Development Goals (SDGs). Conclusion: This work serves as a guide to protect and promote the cultural expressions of Manabí, guaranteeing their appreciation for future generations and promoting economic development and interculturality. The connection between preservation and sustainable tourism is key to this objective.